Skindeep Ulysses - Freedman, Ariela (James Joyce quarterly, 2008)
This essay is about Joyce as an epidermist and Joyce as a chronicler and cataloguer of the "skindeep" surfaces of Dublin in Ulysses. The book is crowded with skins: tanned skins, blushing skins, skins enhanced by makeup and creams, skins marked by race or religion, skins legible and visible, skins imagined and inaccessible and associated with both authenticity and disguise. Skin in Joyce becomes, in Steven Connor's terms, in The Book of Skin, "a place of minglings; a mingling of places," a space where medical, cultural, and aesthetic meanings jostle and intersect and are inscribed and projected on the surface that both expresses and conceals the subject. A skin-deep analysis of Ulysses can reveal to us the entanglement of surface and depth that characterizes Joyce's novel.